Rice stem rot Sclerotium hydrophilum Sace isolated and characterized in Southern Karnataka - Chethana, BS; Prasanna Kumar, MK (ORYZA-An International Journal of Rice, 2019)
In the summer season of 2016 and 2017, in some fields of Cauvery command area of Karnataka the rice cropÂ showed stunted growth with brownish to black lesions without distinct margin on stem at the water level duringÂ tillering and reproductive phase . The causal organism was tissue isolated on potato dextrose agar, colonies ofÂ pure cultures showed white mycelium at first and after two days white coloured scelerotial formation startedÂ which later changed to chocolate brown and after five days became black colour. The hyphal width was measured to be within a range of 6 to 10 ïm and binucleate hyphae were observed between the septa. Small,Â globose and reddish brown to black coloured mature sclerotia measuring 0Â·24-0Â·43 mm were observed in culture. Koch’s postulates was proved by inoculating five days old culture disc containing sclerotia on the stemÂ of 6 week-old healthy rice plants. After seven days symptoms were observed on the inoculated seedlings but not on control plants. The fungus was re-isolated and similar cultural characteristics were observed as of theÂ original culture. DNA fingerprinting of the rDNA-ITS sequence of the representative isolate MNDSR01 (GeneÂ Accession MH393598.1) matched with that of Sclerotium hydrophilum reference (MH393598) with 100%Â identity. To our knowledge, this is the first report of S. hydrophilum in the Cauvery command area of Karnataka.